Chemical genetic inhibition of Mps1 in stable human cell lines reveals novel aspects of Mps1 function in mitosis. - Tale Sliedrecht; Chao Zhang; Kevan M Shokat; Geert J P L Kops (PLoS ONE)
Background Proper execution of chromosome segregation relies on tight control of attachment of chromosomes to spindle microtubules. This is monitored by the mitotic checkpoint that allows chromosome segregation only when all chromosomes are stably attached. Proper functioning of the attachment and checkpoint processes is thus important to prevent chromosomal instability. Both processes rely on the mitotic kinase Mps1. Principal finding We present here two cell lines in which endogenous Mps1 has been stably replaced with a mutant kinase (Mps1-as) that is specifically inhibited by bulky PP1 analogs. Mps1 inhibition in these cell lines is highly penetrant and reversible. Timed inhibition during bipolar spindle assembly shows that Mps1 is critical for attachment error-correction and confirms its role in Aurora B regulation. We furthermore show that Mps1 has multiple controls over mitotic checkpoint activity. Mps1 inhibition precludes Mad1 localization to unattached kinetochores but also accelerates mitosis. This acceleration correlates with absence of detectable mitotic checkpoint complex after Mps1 inhibition. Finally, we show that short-term inhibition of Mps1 catalytic activity is sufficient to kill cells. Conclusions/significance Mps1 is involved in the regulation of multiple key processes that ensure correct chromosome segregation and is a promising target for inhibition in anti-cancer strategies. We report here two cell lines that allow specific and highly penetrant inhibition of Mps1 in a reproducible manner through the use of chemical genetics. Using these cell lines we confirm previously suggested roles for Mps1 activity in mitosis, present evidence for novel functions and examine cell viability after short and prolonged Mps1 inhibition. These cell lines present the best cellular model system to date for investigations into Mps1 biology and the effects of penetrance and duration of Mps1 inhibition on cell viability.